Regression of left ventricular hypertrophy provides an additive physiological benefit following treatment of aortic stenosis: Insights from serial coronary wave intensity analysis. (3rd August 2018) - Broyd, Christopher J.; Rigo, Fausto; Nijjer, Sukhjinder; Sen, Sayan; Petraco, Ricardo; Al‐Lamee, Rasha; Foin, Nicolas; Chukwuemeka, Andrew; Anderson, Jon; Parker, Jessica; Malik, Iqbal S.; Mikhail, Ghada W.; et al.
Abstract: Aim: Severe aortic stenosis frequently involves the development of left ventricular hypertrophy (LVH) creating a dichotomous haemodynamic state within the coronary circulation. Whilst the increased force of ventricular contraction enhances its resultant relaxation and thus increases the distal diastolic coronary "suction" force, the presence of LVH has a potentially opposing effect on ventricular‐coronary interplay. The aim of this study was to use non‐invasive coronary wave intensity analysis (WIA) to separate and measure the sequential effects of outflow tract obstruction relief and then LVH regression following intervention for aortic stenosis. Methods: Fifteen patients with unobstructed coronary arteries undergoing aortic valve intervention (11 surgical aortic valve replacement [SAVR], 4 TAVI) were successfully assessed before and after intervention, and at 6 and 12 months post‐procedure. Coronary WIA was constructed from simultaneously acquired coronary flow from transthoracic echo and pressure from an oscillometric brachial cuff system. Results: Immediately following intervention, a decline in the backward decompression wave (BDW) was noted (9.7 ± 5.7 vs 5.1 ± 3.6 × 10 3 W/m 2 /s, P < 0.01). Over 12 months, LV mass index fell from 114 ± 19 to 82 ± 17 kg/m 2 . Accompanying this, the BDW fraction increased to 32.8 ± 7.2% at 6 months ( P = 0.01 vs post‐procedure) and 34.7 ± 6.7% at 12 months ( P < 0.001 vs post‐procedure). Conclusion: In aortic stenosis, both the outflow tract gradient and the presence of LVH impact significantly on coronary haemodynamics that cannot be appreciated by examining resting coronary flow rates alone. An immediate change in coronary wave intensity occurs following intervention with further effects appreciable with hypertrophy regression. The improvement in prognosis with treatment is likely to be attributable to both features.